Pentatalaksanaan Bedah Myxofibrosarcoma Punggung Kronis: Sebuah Laporan Kasus: Surgical Management of Chronic Myxofibrosarcoma of the Back: A Case Report - Nugroho, Dodhi Kuncoro Setiyo; Lestari, Rinna Dwi; Sukowati, Eko Gunawan (Chakra Brahmanda Lentera Institute, 2026)
Soft tissue sarcoma is a rare malignant tumor that can arise in various parts of the body, including the back. One of its subtypes, myxofibrosarcoma, is known for its relatively slow growth but high risk of local recurrence, making early diagnosis and appropriate management crucial. This case report aims to describe the diagnostic process, surgical management, and functional as well as aesthetic outcomes in a patient with back myxofibrosarcoma. This study used a descriptive case report design involving a 63-year-old male patient who presented with a back mass that had been developing for approximately 20 years. The observed variables included the clinical characteristics of the mass, anatomical pathology findings, type of surgical intervention, and postoperative condition. The assessment tools consisted of clinical physical examination, histopathological evaluation of tumor tissue, and observation of functional outcomes and the patient’s ability to perform daily activities after surgery. The examination results revealed a large soft tissue mass with dilated blood vessels on the back. Anatomical pathology confirmed a malignant mesenchymal tumor suggestive of myxofibrosarcoma. The patient underwent wide excision followed by flap reconstruction. Postoperatively, the patient’s general condition was stable without significant complications, the surgical wound improved, and the patient was able to return to normal activities as a construction worker after routine follow-up and care. This case demonstrates that soft tissue sarcoma of the back, although progressive in appearance and often concerning, can yield good clinical outcomes when managed with adequate surgical intervention according to indications. Patient education regarding the potential success of therapy plays an important role in improving treatment adherence, trust in medical procedures, and optimization of postoperative functional and aesthetic results.